Which type of 5-hydroxytryptamine receptor mediates relaxation of the longitudinal muscle of guinea pig proximal colon in vitro? - Sevcík, J; Ruzicka, V; Slánsky, J; Masek, K (Methods and findings in experimental and clinical pharmacology, 1996)
Concentration-dependent 5-hydroxytryptamine (5-HT) relaxations of guinea pig proximal colon were evoked in the presence of atropine (0.2 microM). 5-HT effect was neuronally mediated since it was blocked by tetrodotoxin (TTX) (0.5 microM). The type of 5-HT receptor mediating the relaxations was investigated using both 5-HT agonists and antagonists. Selective 5-HT3 antagonists tropisetron (10, 50, 500 nM) and ondansetron (1 microM) shifted the concentration-response curves for 5-HT to the right. Another 5-HT3 antagonist MDL 72222 (0.5 microM), 5-HT1/5-HT2 antagonists methiothepin (0.1 microM) and metergoline (0.1 microM), 5-HT(1A,B) antagonist propranolol (l microM) and 5-HT1B antagonist isamoltane (10 nM) were ineffective. Specific agonist of 5-HT3 receptors 2-methyl-5-hydroxytryptamine (2-methyl-5-HT) and agonist of 5-HT1 receptors 5-carboxamidotryptamine (5-CT) also relaxed the preparation, although the relaxation was not 5-HT relaxation. Neither was it neurogenic because it persisted in the presence of TTX (0.5 microM). The concentration-response curve for 2-methyl-5-HT was not affected by ondansetron (1 microM) or tropisetron (0.5 microM), but it was shifted to the right in the presence of 5-HT1/5-HT2 receptor antagonists methiothepin (0.1 microM) and metergoline (0.1 microM) and in the presence of 5-HT(1Da)/5-HT2A receptor antagonist ketanserin (1 microM). Methiothepin (0.1 microM) also inhibited the relaxations evoked in the presence of 5-CT. Specific agonist of 5-HT4 receptors 5-methoxytryptamine did not exert any effect on the preparation. It is suggested that there are two different mechanisms of relaxation in the guinea pig proximal colon. One is neurogenic and involves the activation of 5-HT3 receptors located on inhibitory neurons to the muscle; the other is myogenic and might be mediated via yet unclassified 5-HT receptors located on the muscle.
Keywords: Animals; Indoles; kolon; vztah mezi dávkou a účinkem léčiva; Tropisetron; indoly; antagonisté serotoninu; metergolin; svalová kontrakce; ketanserin; In Vitro Techniques; ondansetron; Serotonin; Receptors, Serotonin; Colon; techniky in vitro; serotonin; Methiothepin; Muscle Relaxation; morčata; tropisetron; Serotonin Receptor Agonists; Dose-Response Relationship, Drug; relaxace svalu; Male; Tetrodotoxin; Ondansetron; receptory serotoninové; agonisté serotoninových receptorů; tetrodotoxin; Metergoline; Guinea Pigs; hladké svalstvo; zvířata; mužské pohlaví; Serotonin Antagonists; Muscle Contraction; Ketanserin; methiothepin; Muscle, Smooth